Students’ Belief Biases Concerning Climate Change and Factors Considered While Evaluating Informal Reasoning Arguments - Perihan Gunes (Journal of Education in Science, Environment and Health)
This study determines whether 9th-grade students have belief biases about the cause of climate change. Furthermore, it determines the factors considered while evaluating the informal arguments about climate change. This study employs a case study, a qualitative research method. Participants included 137 9th-grade students (76 females, 61 males) from three different high schools located in the central district of the city of Aksaray, Turkey. Four types of arguments for climate change were considered: strong-believable, weak-believable, strong-unbelievable, and weak-unbelievable. Each argument contained two questions. One of the questions was related to the strength (strong, weak) of the argument, while the other was linked to the reason why students considered an argument to be weak or strong. The data were analyzed using descriptive statistics and content analysis. As a result, the findings showed that students evaluated various argument types in different ways. Students considered the strong-believable arguments to be the strongest. This was followed by weak-believable, strong-unbelievable, and weak-unbelievable arguments with diminishing strength. The students showed a weak tendency for the argument-based evaluation concerning the reasons for the strength and weak of arguments that included logical reasoning between premises and conclusions. Most of the students focused on the assertion-based evaluations that include the reality of premises and conclusion rather than the relationship between the premises and conclusions. This was followed by the arguments focusing on the relation between the conclusion and premise as well as alternative evaluations independent from the argument and those that considered the different aspects of the issue.